The Search for Peace and Security in Africa: A Comparative Study of NPP-NDC Foreign Policy towards the ECOWAS 2001-2017 - Tetteh, A. (University of Ghana, 2020)
The fundamental elements required for the growth and development of any country are peace and adequate security. West Africa has been characterized by violent conflicts for the past two decades. ECOWAS has taken the lead in establishing several protocols and institutions to curb the numerous security threats that confront the sub-region. The activities of ECOWAS are made possible through the contributions of member countries which Ghana is not an exception. Ghana after the attainment of independence has pursued several policies to champion the collective interest of the African continent and the West African sub-region particularly in the resolution of the myriads of conflicts and security threats in the region. Using the neoliberal institutionalism and historical institutionalism theories, the study sought to comparatively study the foreign policies pursued by NPP and NDC (2001-2017) administration’ towards the peace and security operations of ECOWAS, strategies deployed, and an analysis of continuities and changes in these policies. Data collected from the interviews, review of important literature and an analysis of the statements and speeches of the three former Presidents of NPP and NDC (2001-2017) using the qualitative research methodology revealed that, both governments pursued several policies towards ECOWAS’ peace and security operations. Also, both administrations supported peacekeeping and peacemaking processes of the sub-regional body. An analysis of continuities and changes in their policies revealed that some levels of continuities in their foreign policies are discernible. However, both regimes portrayed some changes in their policies as a result of a lack of a single policy document to guide Ghana’s foreign policies pursued towards ECOWAS’ peace and security operations.
MPhil. Political Science
Keywords: ECOWAS; West Africa; Conflicts; Ghana; NPP; NDC